Early recanalization in large-vessel occlusion stroke patients transferred for endovascular treatment. (13th May 2021) - Arrarte Terreros, Nerea; Bruggeman, Agnetha A E; Swijnenburg, Isabella S J; van Meenen, Laura C C; Groot, Adrien E; Coutinho, Jonathan M; Roos, Yvo B W E M; Emmer, Bart J; Beenen, Ludo F M; van Bavel, Ed; Marquering, Henk A; Majoie, Charles B L M
Abstract : Background: We performed an exploratory analysis to identify patient and thrombus characteristics associated with early recanalization in large-vessel occlusion (LVO) stroke patients transferred for endovascular treatment (EVT) from a primary (PSC) to a comprehensive stroke center (CSC). Methods: We included patients with an LVO stroke of the anterior circulation who were transferred to our hospital for EVT and underwent repeated imaging between January 2016 and June 2019. We compared patient characteristics, workflow time metrics, functional outcome (modified Rankin Scale at 90 days), and baseline thrombus imaging characteristics, which included: occlusion location, thrombus length, attenuation, perviousness, distance from terminus of intracranial carotid artery to the thrombus (DT), and clot burden score (CBS), between early-recanalized LVO (ER-LVO), and non-early-recanalized LVO (NER-LVO) patients. Results: One hundred and forty-nine patients were included in the analysis. Early recanalization occurred in 32% of patients. ER-LVO patients less often had a medical history of hypertension (31% vs 49%, P=0.04), and more often had clinical improvement between PSC and CSC (ΔNIHSS −5 vs 3, P<0.01), compared with NER-LVO patients. Thrombolysis administration was similar in both groups (88% vs 78%, P=0.18). ER-LVO patients had no ICA occlusions (0% vs 27%, P<0.01), more often an M2 occlusion (35% vs 17%, P=0.01), longer DT (27 mm vs 12 mm, P<0.01), shorter thrombi (17 mm vs 27 mm, P<0.01), and higher CBS (8 vs 6, P<0.01) at baseline imaging. ER-LVO patients had lower mRS scores (1 vs 3, P=0.02). Conclusions: Early recanalization is associated with clinical improvement between PSC and CSC admission, more distal occlusions and shorter thrombi at baseline imaging, and better functional outcome.